On Subordinations for Certain Multivalent Analytic Functions in the Right-Half Plane. (17th May 2016) - Xu, Yi-Hui; Liu, Jin-Lin
Abstract : The object of the present paper is to investigate some properties of multivalent analytic functions associated with the lemniscate of Bernoulli.